Addition of Pineapple Peel Silage Liquid Through Drinking Water On The Physical Quality Of Quail Eggs - Harahap, Anwar Efendi; Mucra, Dewi Ananda; Saleh, Eniza; Ardiandi, Ardiandi (Animal Husbandry Study Program, Faculty of Agriculture, Timor University, 2025)
Natural liquid probiotic products have the potential as an alternative feed additive to laying quail which is given through drinking water. This probiotic product can be obtained from pineapple peel waste that has undergone a silage process. The aim of this research was to determine the effectiveness of natural liquid probiotics derived from pineapple peel silage (SKN) on the quality of laying quail eggs. The research method was experimental with a Completely Randomized Design (CRD) consisting of 5 treatments with 4 replications. The treatments applied were: The treatments given were S0 (drinking water without probiotics); S1 (0.5% commercial probiotic via drinking water); S2 (1% SKN liquid probiotics through drinking water), P3 (2% SKN liquid probiotics through drinking water); P4 (3% SKN liquid probiotics through drinking water). The parameters measured are egg weight, egg white index, egg yolk index, and haugh units. The results of the study showed that giving SKN fluid at different levels did not have a significant effect (P>0.05) on egg weight (10.48-10.57 grams/piece), egg white index (0.055-0.056), egg yolk index. (0.41-0.42), and unit height (106.26-107.19). The research conclusion was that the addition of SKN probiotic fluid up to a level of 3% through drinking water was able to maintain the physical quality of quail eggs which included egg weight, egg white index, egg yolk index and haugh units.